Effects of atrioventricular asynchrony on platelet activation: implication of thromboembolism in paced patients. Issue 4 (1st October 1997) - Lau, Chu-Pak; Tse, Hung-Fat; Cheng, Gregory
Abstract : Objective: To investigate the platelet activation in different modes of pacing in patients implanted with dual chamber rate adaptive pacemaker (DDDR) for bradyarrhythmias, and to explore the possible underlying mechanism of the higher thromboembolic incidence in single chamber ventricular rate adaptive (VVIR) pacing. Design: Platelet activation was determined in chronically paced patients during three different pacing modes (VVIR, DDD, and DDDR) in a randomised crossover fashion. Setting —Pacemaker clinic at a university teaching hospital. Patients —15 patients with complete heart block, mean (SD) age 63 (10) years, and 12 patients with sick sinus syndrome, mean age 68 (9) years, implanted with DDDR pacemakers. Main outcome measures: Platelet activation was assessed by measuring the plasma concentrations of platelet factor 4 (PF4) and β thromboglobulin using an enzyme linked immunosorbent assay (elisa ). Mean log plasma PF4 and β thromboglobulin values were compared in paced patients during different pacing modes and with control. Results: Compared with controls, patients paced in DDDR, DDD, and VVIR modes had higher mean log plasma concentrations of PF4 (0.90 (0.32), 0.92 (0.29), and 1.12 (0.33) v 0.61 (0.29) log IU/ml, all p < 0.05, respectively) and β thromboglobulin (1.55 (0.20), 1.59 (0.16), and 1.71 (0.18) v 1.40 (0.12) log IU/ml, all p < 0.05, respectively). In paced patients, VVIR pacing was associated with higher plasma concentrations of PF4 and β thromboglobulin than either DDDR or DDD pacing (all p < 0.05). There was no significant difference in plasma PF4 and β thromboglobulin between patients with complete heart block and sick sinus syndrome in the corresponding pacing mode. Holter monitoring showed no difference in mean pacing rate and occurrence of cardiac arrhythmias to account for the increased platelet activation during VVIR pacing. There was no relation between the percentage of ventricular pacing on Holter during DDDR, DDD, and VVIR modes and the log mean plasma concentrations of PF4 ( r = 0.002, 0.001, and 0.001, respectively, all p > 0.05) and β thromboglobulin ( r = 0.007, 0.01, and 0.001, respectively, all p > 0.05). Conclusions —Single chamber ventricular pacing was associated with enhanced spontaneous systemic platelet activation compared with physiological dual chamber pacing. This was related to the loss of atrioventricular synchrony rather than to the underlying cause of bradycardia, lack of rate response, or coexisting arrhythmia. This abnormality may be associated with increased thromboembolism and was correctible by an appropriate pacing mode prescription and possibly antiplatelet treatment.